Desde el ser a lo dado y desde lo dado al ser : algunos comentarios sobre el significado del trascendentalismo ideal en Kant y Husserl - Luft, Sebastian (Investigaciones Fenomenológicas, 2007)
This paper takes a fresh look at a classical theme in philosophical scholarship, the meaning of transcendental idealism, by contrasting Kant's and Husserl's versions thereof. I present Kant's transcendental idealism as a theory distinguishing between the world as in-itself and as given to the experiencing human being. This reconstruction provides the backdrop for Husserl's transcendental phenomenology as a brand of transcendental idealism expanding on Kant: Through the phenomenological reduction Husserl universalizes Kant's transcendental philosophy to an eidetic science of subjectivity. He thereby furnishes a new sense of transcendental philosophy, rephrases the 'quid iuris?,' and provides a new conception of the thing-in-itself. What needs to be clarified is not exclusively the possibility of a priori cognition, but instead, starting much lower, the validity of objects that give themselves in experience. The thing-in-itself is not an unknowable object, but the idea of the object in all possible appearances experienced at once. In all these innovations Husserl remains committed to the basic sense of Kant’s Copernican Turn. I end with some comments on how both Kant and Husserl view the relation between theoretical and moral philosophy